Análisis de calidad de la energía y estado de carga en un puesto de seccionamiento y transformación de energía (2020)
This work presents the application of a procedure for the analysis of energy quality, specific to voltage deviation and unbalance, in a sectioning and energy transformation (PT) station, as well as evaluating the state of charge of its main elements. In order to carry out the procedure, it is not necessary to carry out invasive or very expensive tests.The work describes the steps of the procedure and deals with the main theoretical aspects applied to stories such as power quality problems, with emphasis on voltage imbalance and deviation.The procedure is applied in the (PT) of the Torre do Tombo neighborhood, in the city of Namibe, belonging to the National Electricity Company (ENE) of the Republic of Angola. For each voltage and current reading, the parameters and curves that allowed evaluating the state of charge of the transformer, the circuit breakers and the conductors of each circuit of the (PT) were determined, as well as performing an analysis of the power quality of one of the circuits, detecting power quality problems and poor selection of circuit breakers.